High-temperature tensile and thermal shock characterization of low-temperature rolled tungsten. (March 2023) - Ma, Xiaolei; Zhang, Xiaoxin; Feng, Fan; Wang, Ting; Liu, Xiang; Wang, Jianbao; Lv, Wei; Lang, Shaoting; Ge, Changchun; Yan, Qingzhi
Highlights: Batch-producible W plates were prepared by powder metallurgy plus low-temperature rolling technology. The low-temperature rolled-PW shows excellent strength and plasticity simultaneously, good thermal conductivity and wonderful transient thermal shock resistance. Low-temperature rolling technology can be employed directly in mass production of W-based materials with large scale, which is urgent for ITER and other nuclear fusion installations. This work provides important reference value for the development of fusion materials. Abstract: A developed tungsten (W) grade was prepared by powder metallurgy technology plus multi-step low-temperature rolling. The relative density, thermal conductivity, microstructure, tensile properties of original and high-temperature annealed states, micro-hardness and transient thermal shock resistance were characterized. The results of tensile test with a strain rate of 2 × 10 -4 s −1 show that the ductile–brittle transition temperature (DBTT) of rolled-W in the original and recrystallized state are 150–200 °C and 250–300 °C, respectively. The rolled-W presents high strength and great plasticity simultaneously. For example, the maximum ultimate tensile strength (UTS) below DBTT is as high as ∼ 1189 MPa, and the maximum total elongation (TE) above DBTT reaches 28.9 %. In particular, the TE of recrystallized W achieves an incredible 81.4 % at 500 °C, which is the highest value among all the published literatures so far. The results of transient thermal shock tests indicate that the rolled-W has an outstanding transient thermal shock resistance. It can withstand the thermal bombardment at an absorbed power densities (APD) of 0.33 GW·m −2 without causing any surface damages, and still no cracks are observed as the APD rises to 0.88 GW·m −2 . Moreover, the failure mechanism of rolled-W was also studied in details. This work plays an important role in establishing a dependable China Fusion Engineering Test Reactor (CFETR) data-library on a unitary W grade, which can provide an effective reference for the identification of material performance under the high heat flux and subsequent numerical simulation.